ANALISIS KELAYAKAN INSTRUMEN BERPIKIR KREATIF SISWA PADA MATERI FLUIDA STATIS - Ani Rahmadani Hasibuan; Desnita; Hidayati; Fuja Novitra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The ability to think creatively is one of the achievements of the 21st century that needs to be measured accurately through valid and reliable instruments. Therefore, before being used in research, the creative thinking ability test instrument needs to go through a testing process to ensure that the instrument is able to measure the ability in question accurately and consistently. This study aims to analyze the feasibility of creative thinking ability test instruments on Static Fluid materials through content validity, empirical validity, and reliability tests. This study uses a quantitative approach with a descriptive method. The research subjects consisted of three validators who were lecturers of Physics Education at Padang State University and 30 students in grade XII of SMA Pembangunan Laboratory UNP. The research instrument is in the form of an expert validation sheet consisting of 22 statement items and a creative thinking ability test in the form of six phenomena-based essay questions which are developed into 18 questions based on critical thinking indicators according to Facione, namely interpretation, analysis, evaluation, and inference. The validity of the contents was analyzed using the Aiken's V index, the validity of the item was used Pearson's Product Moment correlation, while the reliability of the instrument was analyzed using Cronbach's Alpha coefficient. The results showed that the validity of the content of the instrument obtained an Aiken's V value ranging from 0.7222–0.8000 so that all aspects of the assessment met the valid criteria. The results of the empirical validity test showed that of the 18 questions tested, as many as 15 questions were declared valid and 3 questions were declared invalid. Furthermore, the results of the reliability test on 15 valid questions obtained a Cronbach's Alpha value of 0.955 in the very high category. Thus, the critical thinking ability test instrument developed has met the criteria of validity and reliability so that it is suitable for use as a research instrument to measure students' creative thinking skills in Static Fluid material.